Drift paths of ions composing multiple‐nose spectral structures near the inner edge of the plasma sheet. Issue 22 (21st November 2016) - Ferradas, C. P.; Zhang, J.‐C.; Spence, H. E.; Kistler, L. M.; Larsen, B. A.; Reeves, G.; Skoug, R.; Funsten, H.
Abstract: We present a case study of the H +, He +, and O + multiple‐nose structures observed by the Helium, Oxygen, Proton, and Electron instrument on board Van Allen Probe A over one complete orbit on 28 September 2013. Nose structures are observed near the inner edge of the plasma sheet and constitute the signatures of ion drift in the highly dynamic environment of the inner magnetosphere. We find that the multiple noses are intrinsically associated with variations in the solar wind. Backward ion drift path tracings show new details of the drift trajectories of these ions; i.e., multiple noses are formed by ions with a short drift time from the assumed source location to the inner region and whose trajectories (1) encircle the Earth different number of times or (2) encircle the Earth equal number of times but with different drift time, before reaching the observation site. Key Points: Ion multiple‐nose structures are often observed near the inner edge of the plasma sheet The multiple energy bands are intrinsically associated with variations in the solar wind Ions composing the multiple noses drift different numbers of times around the Earth in a similar time frame